(untitled) (Prithvi Academic Journal, 2024)
The indigenous communities remain in close, harmonious, and respectful relationship with nature. They acknowledge nature as nourishing mother and a source of energy that gives life to each and every being on earth. The Tamang, one of the indigenous communities of Nepal, shares intricately closer ties with nature. They worship nature and wish to remain under the ever oozing blessing of mother earth. The popular folk narratives and myths among the Tamangs illustrate immense respect and appreciation of nature, which are mostly sung by Tamba, the spokesperson of Tamang community. This paper examines eco-consciousness of Tamang community in the selected songs of Tamba, which are taken from Shantabir Lama (Pakhrin)’s book Tamba kaiten whai rimthim [Ancestral custom and songs of the Tamangs] (2014). The paper focuses on analyzing Tamangs’ perception of nature and significance of their indigenous knowledge in terms of nature-human harmonious bonding. The paper uses textual analysis to examine the selected songs of Tamba, incorporating the concept of Tamang knowledge and aesthetics to shed light on eco-consciousness of the Tamangs of Nepal.